My home,my country - Barnes L; South Africa (Souh Africa: Awareness Publishing Group (Pyt) Ltd, 2010)
A general introduction to the country of south africa ,including its geographical location, peole,language, weather, resources and transport as well as some of the things that it is famous for
Junior Non-Fiction -;Juvenile Literature